Answer:
Step-by-step explanation:
Answer:
![\frac{sin(3a)-cos(3a)}{sin(a)+cos(a)} =2sin(2a)-1](https://tex.z-dn.net/?f=%5Cfrac%7Bsin%283a%29-cos%283a%29%7D%7Bsin%28a%29%2Bcos%28a%29%7D%20%3D2sin%282a%29-1)
Step-by-step explanation:
we are given
![\frac{sin(3a)-cos(3a)}{sin(a)+cos(a)} =2sin(2a)-1](https://tex.z-dn.net/?f=%5Cfrac%7Bsin%283a%29-cos%283a%29%7D%7Bsin%28a%29%2Bcos%28a%29%7D%20%3D2sin%282a%29-1)
we can simplify left side and make it equal to right side
we can use trig identity
![sin(3a)=3sin(a)-4sin^3(a)](https://tex.z-dn.net/?f=sin%283a%29%3D3sin%28a%29-4sin%5E3%28a%29)
![cos(3a)=4cos^3(a)-3cos(a)](https://tex.z-dn.net/?f=cos%283a%29%3D4cos%5E3%28a%29-3cos%28a%29)
now, we can plug values
![\frac{(3sin(a)-4sin^3(a))-(4cos^3(a)-3cos(a))}{sin(a)+cos(a)}](https://tex.z-dn.net/?f=%5Cfrac%7B%283sin%28a%29-4sin%5E3%28a%29%29-%284cos%5E3%28a%29-3cos%28a%29%29%7D%7Bsin%28a%29%2Bcos%28a%29%7D%20)
now, we can simplify
![\frac{3sin(a)-4sin^3(a)-4cos^3(a)+3cos(a)}{sin(a)+cos(a)}](https://tex.z-dn.net/?f=%5Cfrac%7B3sin%28a%29-4sin%5E3%28a%29-4cos%5E3%28a%29%2B3cos%28a%29%7D%7Bsin%28a%29%2Bcos%28a%29%7D%20)
![\frac{3sin(a)+3cos(a)-4sin^3(a)-4cos^3(a)}{sin(a)+cos(a)}](https://tex.z-dn.net/?f=%5Cfrac%7B3sin%28a%29%2B3cos%28a%29-4sin%5E3%28a%29-4cos%5E3%28a%29%7D%7Bsin%28a%29%2Bcos%28a%29%7D%20)
![\frac{3(sin(a)+cos(a))-4(sin^3(a)+cos^3(a))}{sin(a)+cos(a)}](https://tex.z-dn.net/?f=%5Cfrac%7B3%28sin%28a%29%2Bcos%28a%29%29-4%28sin%5E3%28a%29%2Bcos%5E3%28a%29%29%7D%7Bsin%28a%29%2Bcos%28a%29%7D%20)
now, we can factor it
![\frac{3(sin(a)+cos(a))-4(sin(a)+cos(a))(sin^2(a)+cos^2(a)-sin(a)cos(a)}{sin(a)+cos(a)}](https://tex.z-dn.net/?f=%5Cfrac%7B3%28sin%28a%29%2Bcos%28a%29%29-4%28sin%28a%29%2Bcos%28a%29%29%28sin%5E2%28a%29%2Bcos%5E2%28a%29-sin%28a%29cos%28a%29%7D%7Bsin%28a%29%2Bcos%28a%29%7D%20)
![\frac{(sin(a)+cos(a))[3-4(sin^2(a)+cos^2(a)-sin(a)cos(a)]}{sin(a)+cos(a)}](https://tex.z-dn.net/?f=%5Cfrac%7B%28sin%28a%29%2Bcos%28a%29%29%5B3-4%28sin%5E2%28a%29%2Bcos%5E2%28a%29-sin%28a%29cos%28a%29%5D%7D%7Bsin%28a%29%2Bcos%28a%29%7D%20)
we can use trig identity
![sin^2(a)+cos^2(a)=1](https://tex.z-dn.net/?f=sin%5E2%28a%29%2Bcos%5E2%28a%29%3D1)
![\frac{(sin(a)+cos(a))[3-4(1-sin(a)cos(a)]}{sin(a)+cos(a)}](https://tex.z-dn.net/?f=%5Cfrac%7B%28sin%28a%29%2Bcos%28a%29%29%5B3-4%281-sin%28a%29cos%28a%29%5D%7D%7Bsin%28a%29%2Bcos%28a%29%7D%20)
we can cancel terms
![=3-4(1-sin(a)cos(a))](https://tex.z-dn.net/?f=%3D3-4%281-sin%28a%29cos%28a%29%29)
now, we can simplify it further
![=3-4+4sin(a)cos(a))](https://tex.z-dn.net/?f=%3D3-4%2B4sin%28a%29cos%28a%29%29)
![=-1+4sin(a)cos(a))](https://tex.z-dn.net/?f=%3D-1%2B4sin%28a%29cos%28a%29%29)
![=4sin(a)cos(a)-1](https://tex.z-dn.net/?f=%3D4sin%28a%29cos%28a%29-1)
![=2\times 2sin(a)cos(a)-1](https://tex.z-dn.net/?f=%3D2%5Ctimes%202sin%28a%29cos%28a%29-1)
now, we can use trig identity
![2sin(a)cos(a)=sin(2a)](https://tex.z-dn.net/?f=2sin%28a%29cos%28a%29%3Dsin%282a%29)
we can replace it
![=2sin(2a)-1](https://tex.z-dn.net/?f=%3D2sin%282a%29-1)
so,
![\frac{sin(3a)-cos(3a)}{sin(a)+cos(a)} =2sin(2a)-1](https://tex.z-dn.net/?f=%5Cfrac%7Bsin%283a%29-cos%283a%29%7D%7Bsin%28a%29%2Bcos%28a%29%7D%20%3D2sin%282a%29-1)
Answer:
![( - 4 \\ - 3](https://tex.z-dn.net/?f=%28%20-%204%20%5C%5C%20%20-%203)
Step-by-step explanation:
4unity to the left
3unity down
The economy of India is a developing mixed economy. It is the world's sixth-largest economy by nominal GDP and the third-largest by purchasing power parity (PPP).